Seleção de genótipos de cucurbitaceas a Monosporascus cannonballus e compatibilidade de portaenxertos - Demartelaere, Andréa Celina Ferreira (Universidade Federal Rural do Semi-Árido, 2011)
The Cucurbitaceae have a great economic importance, having a relevant participation in several countries around the world. In Brazil, specifically in the Northeast region are concentrated the largest producers of melon and watermelon. With the intensification of these crops, together with several inadequate management practices, it has been observed an increase in incidence of root diseases in cucurbitaceae, caused by soilborne fungi. From among these pathogens, worth mentioning the Monosporascus cannonballus, causer of the decline of branches in major producer areas of melon and watermelon of Rio Grande do Norte, responsible for causing heavy losses. However, research has been intensified with different methods of control, with the use of chemical fumigants, antagonists fungus for biological control; solarization, grafting and genetic control. Therefore, the objectives of this paper, were: to select genotypes of curubitaceae resistants to the M. cannonballus and check the fixation of rootstocks of pumpkins over grafting of watermelon. In the first experiment, we analyzed the damage on the roots in genotypes of pumpkins, watermelons and melons, and initial and final population of soil ascospores, evaluating the resistance of these M. cannonballus. At the second experiment was evaluated fixation, stem diameter, plant height, leaf number, fresh mass of the aerial part, fresh mass of the root, dry mass of shoot and root in pumpkin rootstocks on the graft watermelon. The statistical outline adopted in both experiments was entirely randomized. The genotypes were classified as resistant and moderately resistant. The resistants were: [(PES-07, PEC-01, PEK-05, TPR-08689, Shintoza and Fitó Pumpkin - Pumpkins), (TPR-02978 - watermelon), (TPR-05851, TPR-06827, PEM-06 and PED-02 - melons)]. The genotype TPR- 04329 (melon) and the commercial cultivar Moranga (pumpkin) were mildly resistant. The rootstocks of pumpkins PEK-05, PEC-01 and PES-07 showed less final concentration of ascospores in soil. The rootstock of the pumpkin PEC-01 on graft from commercial cultivar Crimson Sweet watermelon, showed the highest rate of fixation and better results in variables, plant height, leaf number and stem diameter.
Genotype selection cucurbit the Monosporascus cannonballus and compatibility rootstocks
Keywords: Cucurbita moschata; Fungi in habitant of soil; Grafting; Cucurbita moschata; Fungo habitante de solo; Enxertia; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA